Efficacy of Streptococcus salivarius Blis K12 in the Prevention of Upper Respiratory Tract Infections in Physically Active Individuals: A Randomized Controlled Trial - Alexander Bertuccioli; Marco Cardinali; Matteo Micucci; Marco Bruno Luigi Rocchi; Chiara Maria Palazzi; Giordano Bruno Zonzini; Giosuè Annibalini; Annalisa Belli; Davide Sisti (Microorganisms)
This study investigates the efficacy of Streptococcus salivarius K12 in preventing upper respiratory tract infections (URTIs) in healthy adults. URTIs are a common issue, particularly in physically active individuals, leading to significant disruptions in daily life. Probiotics, such as S. salivarius K12, have emerged as a potential preventive strategy for these infections. This research was conducted as a randomized, double-blind, placebo-controlled trial involving 112 participants aged between 19 and 25. Participants were randomly divided into two groups: one group received a daily dose of S. salivarius K12, marketed as Bactoblis®, while the other received a placebo. The trial lasted for four months, during which adherence to the treatment protocol was closely monitored. The primary goal was to measure the incidence of URTIs using the Jackson Scale and the Wisconsin Upper Respiratory Symptom Survey (WURSS-11). The results indicated that higher adherence to the S. salivarius K12 treatment was associated with an increased number of days without URTI symptoms. Although the overall severity of symptoms did not differ significantly between the treatment and control groups, those with high adherence to S. salivarius K12 (greater than 90%) reported more days free from illness. In conclusion, S. salivarius K12 demonstrated potential as a preventive measure against URTIs, especially in individuals who adhered strictly to the treatment regimen. However, further research involving larger populations and longer follow-up periods is needed to fully confirm these findings and better understand the role of S. salivarius K12 in preventing respiratory infections.